The hybrid outcome of urban change: global city, polarized city? - Ayat Ismail (Glocalism: Journal of Culture, Politics and Innovation)
A wide range of studies supports the assumption that levels of socio-spatial polarization, segregation, and exclusion are rising in global cities over the past decades as a direct outcome of certain global processes, such as the deindustrialization process, its associated changes in division of labor, and declined redistributive power of the welfare state. However, that assumption – known as the polarization thesis – is criticized based on several contentions, including the oversimplification of the global/local interplay by overlooking the role of local contingent factors that may modify, intensify, or reverse the expected socio-spatial outcome in individual cities. This study aims to capture the hybrid nature of the socio-spatial outcomes of global cities by proving that the complex process of restructuring of cities is a form of structural and chronological hybridity.